Pott’s Puffy Tumor: a need for interdisciplinary diagnosis and treatment. German Version Pott-Puffy-Tumor: die Notwendigkeit einer interdisziplinären Diagnostik und Behandlung - Kühn, Jan Philipp; Linsler, Stefan; Nourkami-Tutdibi, Nasenien; Meyer, Sascha; Becker, Sören L.; Yilmaz, Umut; Schick, Bernhard; Bozzato, Alessandro; Kulas, Philipp (HNO, 2022)
Pott’s puffy tumor (PPT) is an infection of the frontal sinus with subperiosteal and intracranial abscess formation and one of the rare entities in pediatrics. We present a series of four cases of PPT that occurred in two children (6 and 9 years) and in two young adults (17 and 19 years). All patients were treated by an interdisciplinary team of pediatric, neurosurgical, ENT, radiological, and neuroradiological specialists. Antibiotic treatment was combined with single endoscopic surgery in one case and combined endoscopic sinus surgery with an open transcranial approach to drain intracranial abscess formation in three cases. It is important to be aware that PPT occurs in children with the finding of intracranial abscess formation. Therefore, a close interdisciplinary cooperation for successful treatment is needed in this rare disease.
CRIS-Team Scopus Importer:2023-12-20
Keywords: Adolescents; Children; Frontal bone; Frontal subperiosteal abscess; Osteomyelitis